1993
DOI: 10.1007/bf00202568
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hand tremor time series

Abstract: Tremor is classified into physiological, essential, and parkinsonian tremor by means of clinical criteria. The aim of our work was to extract quantitative features from the measurements of the acceleration of human postural hand tremor. Different mathematical methods were adopted and modified in order to separate these three types of tremor. Best discrimination between physiological and pathological tremors has been achieved by methods distinguishing nonlinear from linear behavior. On the other hand, methods s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(51 citation statements)
references
References 12 publications
0
48
0
Order By: Relevance
“…63 Several studies demonstrated absent frequency reduction after loading of the trembling limb in PD patients. 33,64 Another series of studies has dealt with resetting of the rhythm of parkinsonian tremor after different stimuli as mechanical perturbations, 65 electrical stimulation of the median nerve, 66,67 or transcranial magnetic stimulation of the motor cortex. 68 The results did not show a consistent resetting of the tremor rhythm when stimulating the periphery but a complete resetting when the cortex was stimulated.…”
Section: Contribution Of Reflex Pathwaysmentioning
confidence: 99%
“…63 Several studies demonstrated absent frequency reduction after loading of the trembling limb in PD patients. 33,64 Another series of studies has dealt with resetting of the rhythm of parkinsonian tremor after different stimuli as mechanical perturbations, 65 electrical stimulation of the median nerve, 66,67 or transcranial magnetic stimulation of the motor cortex. 68 The results did not show a consistent resetting of the tremor rhythm when stimulating the periphery but a complete resetting when the cortex was stimulated.…”
Section: Contribution Of Reflex Pathwaysmentioning
confidence: 99%
“…It is an adapted version of the fourth statistical moment proposed by Timmer et al [1993] and corresponds to the mean absolute values of tremor time series (with their mean set to zero [Beuter et al, 2003]). See Figure 5 for further explanation.…”
Section: For Postural and Kinetic Tremorsmentioning
confidence: 99%
“…For instance, linear analyses may also reveal aspects of nonlinear coupling in ET (Timmer et al, 1993. Furthermore, nonlinear interdependencies are not necessarily superior but rather assess distinct aspects of signal coupling.…”
Section: Methodological Considerationsmentioning
confidence: 99%